ANALISIS SISTEM DAN METODE PENGUMPULAN ZAKAT PENGHASILAN APARATUR SIPIL NEGARA PADA BAZNAS BANYUMAS - Yustisia, Pratiwi (Fakultas Ekonomi dan Bisnis Islam (FEBI), Institut Agama Islam Negeri (IAIN) Purwokerto, 2020)
BPS data on March 2019 shows that poor people in Indonesia reached 25,14 million. It means that there are so many Indonesian people still have not got a decent life both economically and socially. Indonesia is the country with the largest Muslim population, so one of the solutions to overcome the poverty is to encourage zakat intensively. Since 2018, Indonesian government planned to issue the presidential decree about the income zakat collection of 2,5 percent for muslim civil servants. In Banyumas, this regulation has been applied since August 2018, after the circular letter No.159/BP.BAZNASBMS/VII/2018 released on July 9th 2018 from BAZNAS Banyumas that contains an appeal for civil servants to pay zakat when their income has reached a certain nishab according to the Decision of Head of BAZNAS No. KEP.016/BP/BAZNAS/ XII/2015. In that decision stated that the value of nishab income is considered the same with the agricultural yields that has a three months farming period so the value of nishab is divided by three. That statement is not in line with MUI Fatwa No.3 of 2003 which is using gold nishab. Moreover, that Decision has been updated into Decision of Head of BAZNAS No. 73 of 2017 that set the value of nishab equals to 85 grams of gold, so the Decision of Head of BAZNAS No. KEP.016/BP/BAZNAS/XII/2015 was revoked and no longer enforceable. The study aims to analyze the nishab rules of zakat which is used and understood by MUI, regional governments, BAZNAS, UPZ, and civil servants and also to understand the application of the 8th Zakah Core Principles about Good Amil Governance. This research used qualitative method to analyze further about system and method of income zakat collection that applied to zakat payers in Banyumas Regency. The results showed the inconsistency between the established Baznas Banyumas rules with both Central Baznas rules and MUI Fatwa, and Baznas Banyumas just relies on the Regulation of Minister of Religious Affairs. This appeal must be reviewed immediately with Central BAZNAS and MUI and then informed to all related parties so that they have sharia-compliant understanding about zakat.